The organic triangle cycle experience and status. (September 2017) - Hays, Lance; Welch, Philip; Boyle, Patrick
Abstract: The organic triangle cycle (OTC) incorporates a simple liquid counter-current heat exchanger, eliminating the "pinch point" limitation to heat input to organic Rankine cycle (ORC) systems. A flashing liquid expander is used to generate power from the heated high pressure liquid. Other advantages include direct drive of a 50/60 Hz generator, eliminating a gearbox; and a hermetic generator, eliminating the lube oil system and seals common to many ORC systems. Improvements in power production from the heat sources as much as 20 to 40% have been predicted, subject to the efficiency of the flashing liquid expander and the minimum allowable return temperature of the heat source. Development of a flashing liquid expander, critical to performance of the OTC, has continued for several years. Since that time several applications of the two-phase impulse turbine, known as the Variable Phase Turbine (VPT) were successfully addressed, including the replacement of expansion valves in chillers and industrial applications. Recently the VPT has been applied to OTC systems for waste heat recovery from shipboard engines and to low temperature geothermal power production. Performance and design of OTC systems for those applications is provided. A 300 kW system producing power from hot air at 176 ºC from a turbocharger compressor of a shipboard propulsion engine is described. The working fluid is R245fa. Performance and operational experience are discussed. A 1 MW OTC system was operated with geothermal brine at 113 ºC. The working fluid is R134A. Performance and operational experience are described. In both systems measured performance of VPT agreed with the design code predictions of 73-75% for the conditions of those applications, giving confidence to the viability of many OTC applications. A compact 1 MW system with a hermetic generator designed for power production from a diesel engine exhaust at 325 ºC is shown. The unit is designed also for OTC applications for geothermal and waste heat recovery.